Pollen metabarcoding reveals a broad diversity of plant sources available to farmland flower visitors near tropical montane forest - Montero, B. Karina; Gamboa-Barrantes, Nicole; Rojas-Malavasi, Geovanna; Cristóbal-Perez, E. Jacob; Barrantes, Gilbert; Cascante-Marín, Alfredo; Hanson, Paul; Zumbado, Manuel A.; Madrigal-Brenes, Ruth; Martén-Rodríguez, Silvana; Quesada, Mauricio; Fuchs, Eric J. (Frontiers in Plant Science, 2025)
Despite the widely recognized role of pollinators in ecosystem services, we currently have a poor understanding of the contribution of Natural Protected Areas neighboring agricultural landscapes to crop pollinator diversity and plant-pollinator interactions. Here, we conducted monthly surveys over a period of one year to study the diversity of insect visitors in dominant fruit crops—avocado, plum, apple, and blackberry—and used pollen DNA metabarcoding to characterize the community of plant sources in and around low-intensive farmland bordered by protected montane forest in Costa Rica. We found that crops and native plants had distinct communities of flower visitors, suggesting the presence of fine-scale habitat differences. DNA metabarcoding coupled with a custom-built reference database, enabled us to identify plant sources among pollen samples with high taxonomic resolution (species or genus level). We found that insect visitors carried pollen from a large diversity of plant taxa, including species native to the montane forests and highland páramos of Costa Rica. The diversity and composition of plant sources were variable across fruit crops and insect groups. Wildflower visitors such as bumblebees and syrphid flies, use a diverse range of plant taxa at similar levels to managed honeybees. This indicates the potential contribution of a diverse community of insect visitors to the pollination services of fruit crops and native flora. Overall, our study suggests that low-intensive farming practices that promote the presence of common ruderals combined with nearby protected forests contribute to maintaining diverse insect communities that provide crucial pollination services.